2012
DOI: 10.7205/milmed-d-11-00181
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding Practices in Military Families: A 12-Month Prospective Population-Based Study in the National Capital Region

Abstract: Breastfeeding practices in military families have not been widely investigated. The objective of this study was to measure the prevalence and duration of breastfeeding among uniformed families and identify factors associated with breastfeeding. We conducted a prospective study of 253 mothers of new infants from July to December 2004. Initial information gathered included demographic data, feeding choices, and intended duration of breastfeeding. Follow-up surveys were conducted until 12 months postpartum. 51% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 14 publications
1
24
0
Order By: Relevance
“…A drawback to our data is that it lacks a variable indicating whether or not the mothers are employed. Since the military subsample is comprised primarily of military spouses, a higher number than that of civilians may be out of the labor force, although previous work has found very little to no difference between active duty and military spouse populations in breastfeeding duration [14,22].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A drawback to our data is that it lacks a variable indicating whether or not the mothers are employed. Since the military subsample is comprised primarily of military spouses, a higher number than that of civilians may be out of the labor force, although previous work has found very little to no difference between active duty and military spouse populations in breastfeeding duration [14,22].…”
Section: Discussionmentioning
confidence: 99%
“…Breastfeeding practices among the military family population have received little attention [14,15]. We speculate that such well-known racial disparities may disappear in the military setting.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Another study showed that officers were three times more likely to breastfeed compared to soldiers (21) .…”
Section: Discussionmentioning
confidence: 99%